The osteo-odonto-keratoprosthesis. Issue 4 (July 2017) - Zarei-Ghanavati, Mehran; Avadhanam, Venkata; Vasquez Perez, Alfonso; Liu, Christopher
Abstract : Purpose of review: To describe the practice of and recent developments in the osteo-odonto-keratoprosthesis. Recent findings: Formal psychological assessment and support have been described. A sub-aqua system for fashioning the osteo-odonto-keratoprosthesis lamina; adoption of thicker laminae; use of bisphosphonate drugs; advances in laminar imaging; and use of bone augmentation and bone morphogenetic protein have been described for prevention, detection, and management of laminar resorption. Two systems of optical cylinders available commercially. A stepladder approach to buccal mucous membrane overgrowth onto the optical cylinder has been described, including use of mitomycin-C. Orbital decompression has been used for cosmetic improvement. Detection of glaucoma may be aided by an intraocular pressure sensor, whereas surgical treatment is mainly by way of glaucoma drainage devices, as endolaser ciliary ablation and recti muscle disinsertion and reinsertion not having prolonged and significant long-term beneficial effect. Sublingual timolol has been described. The use of endoscopy has been proposed for preoperative evaluation of the posterior segment, ciliary ablation and for vitreoretinal surgery although wide-angle viewing systems remains standard practice. Summary: The osteo-odonto-keratoprosthesis is the procedure of choice for rehabilitation of corneal blindness for end-stage ocular surface disease, serving a completely different patient group to the Boston Type 1 KPro.